The impact of alternative input subsidy exit strategies on Malawi’s maize commodity market - Mapila, Mariam A.T.J. (International Food Policy Research Institute, 2013)
This study has been conducted in order to generate evidence of the visibility of exit from farm input subsidies in an African context. The study simulates the impact of alternative exit strategies from Malawi’s farm input subsidy program on maize markets. The simulation is conducted using a multiequation partial equilibrium model of the national maize market, which is sequentially linked via a price-linkage equation to local rural maize markets. The model accounts for market imperfections prevailing in the country that arise from government price interventions. Findings show that some alternative exit strategies have negative and sustained impacts on maize yields, production, and acreage allocated to maize over the simulation period. Market prices rise steadily as a result of the implementation of different exit strategies. Despite higher maize prices, domestic maize consumption remains fairly stable, with a slow but increasing trend over the simulation period.